(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
In this article, pencil drawing as the basis of visual art, realistic depiction of existing things and forms, to develop practical knowledge and skills, as well as aesthetic taste. Love for nature, observation, composition, constructive structure, proportions, perspective, laws of light and shadow are important.